Revolutionizing Elementary Education: The Family Literacy Module - Boosting Reading Interest and Skills - Wahyu Laraswati; Aprilia Tina Lidyasari (AL-ISHLAH: Jurnal Pendidikan, 2024)
Literacy is a crucial indicator of educational success. Despite its importance, literacy skills in Indonesia remain suboptimal, as evidenced by various studies and surveys. This research aims to develop a family literacy module designed to enhance elementary school students' interest and reading skills. This study employed the Research and Development (RD) framework using the Borg Gall ten-stage model. Participants included 69 parents and 28 students. Data were collected through observations, questionnaires, and tests to evaluate the module's effectiveness. The developed family literacy module significantly improved students' reading interests and abilities, demonstrating its effectiveness as an educational tool. The study's findings indicate that the family literacy module provides a practical solution for addressing low literacy levels among elementary school students. By engaging both students and parents, the module fosters a supportive reading environment, which is essential for literacy improvement. The family literacy module effectively enhances elementary school students' reading interests and skills, offering a promising strategy for literacy development in Indonesia. Future research should investigate the broader application of this module and assess its long-term impacts on literacy enhancement.